Proapoptotic activity of essential oils from Syzygium aromaticum, Melaleuca cajuputi, and Cymbopogon nardus on HeLa human cervical cancer cells - Happy Kurnia Permatasari, Anita Dominique Subali, Muhammad Yusuf, Holipah Holipah (Journal of Applied Pharmaceutical Science, 2022)
Cancer develops through an imbalance in the cell cycle regulators, resulting in persistent proliferation and escaping apoptosis. Essential oils (EOs) are gaining popularity as a potential natural-based anticancer agent. This research aimed to evaluate cytotoxic activity by induction of apoptosis in Syzygium aromaticum, Melaleuca cajuputi, and Cymbopogon nardus EOs against the HeLa human cervical cancer cell lines. HeLa cell cultures were treated with EOs from three plants separately at 30, 60, and 120 μg/ml and 0 μg/ml as control. The trypan blue exclusion test was conducted to examine cell viability and determine the inhibitory concentration (IC50) value. Cytotoxicity activity was evaluated using Annexin V (AV) and propidium iodide (PI) flow cytometry. The EOs of the three herbs significantly decrease HeLa cells’ viability at 24 and 48 hours after treatment in comparison to the control. AV–PI analysis displayed significant induction of late-stage apoptosis in a dose-dependent relationship. The 48 hour IC50 values of EOs were 18.06 μg/ml (S. aromaticum), 26.25 μg/ml (M. cajuputi), and 28.03 μg/ml (C. nardus). The EOs of S. aromaticum, M. cajuputi, and C. nardus have potential anticancer activity with their cytotoxic effects on HeLa cells and could be explored further as a cervical cancer treatment.
Keywords: Anticancer, apoptosis, cervical cancer, cytotoxic, essential oils, HeLa cell